3 uses of the knife : on the nature and purpose of drama - Mamet, David (Vintage Books, 2000)
What makes good drama? And why does drama matter in an age that is awash in information and entertainment? With bracing directness and aphoristic grace, the Pulitzer Prize-winning playwright of Glengarry Glen Ross delivers a thrillingly original treatise on his art. To David Mamet, human beings are drama-creating animals who impose narrative structures on everything from today's weather to next year's elections. Mamet distinguishes true drama from its false variants, unravels the infamous Second-Act Problem, and considers the mysterious persistence of the soliloquy. Three Uses of the Knife is an inspired guide for any playwright or theatergoer that doubles as a trenchant work of moral and aesthetic philosophy. - Publisher.